Rooster fighter. Volume 1 - Sakuratani, Shu (Viz signature., 2022)
"In a world where terrifying monsters walk the earth, one heroic rooster is destined for greatness. When giant demons threaten the inocent, he's going to show them who's boss! The neighborhood cock of the walk is more than just an ordinary rooster--he's humanity's greatest defender! His opponents may be ten stories tall, but nothing is bigger than his stout heart and his fearsome battle cry-cock-a-doodle-doo!" -- cover.